Utilization of Rembang PLTU Coal Burning Waste for Paving Blocks Material - Bambang Haryadi; Andi Purnomo; Fadhila Rizqina; Tegar Aditya; Mohammad Wahyu Eka; Pangestuti, Endah Kanti (Universitas Negeri Semarang, 2024)
Accumulating coal combustion waste will negatively affect the neighborhood. Over time, more waste will be generated, which will take time. Processing methods are needed to reduce the increasing amount of coal waste. One processing method is to use ash and bottom ash as a mixture in paving. The study used paving blocks as a control sample for one cement : 3 sand. Fly ash addition variation consists of 0%, 10%, 20%, and 30% of the cement weight. The compressive strength test results at 28 days and 60 days of control paving blocks with a standard mixture were 17.8 MPa and 24 MPa. The compressive strength results from 0% variations are 10.9 MPa and 15.6 MPa. The 10% variation has a compressive strength of 10.5 MPa and 13.6 MPa. The 20% variation has a compressive strength of 10.25 MPa and 14.5 MPa. The variation is 30%, with compressive strength of 11.5 MPa and 14.86 MPa.